A COMPARISON BETWEEN SATOYAMA AND THE AINU WAY OF LIFE - Devon Dublin; Noriyuki Tanaka (Universitas Gadjah Mada, 2015)
This study compares the concept of Satoyama with that of the Ainu, with a view of establishing the cultural,ecological and economical similarities between them and to examine the impact of the developmentof Hokkaido on the Ainu human ecology. Research was conducted in the Noto Peninsula, and theHidaka region of Hokkaido. Data was collected through individual, household and group interviews,questionnaire surveys, field visits and available documentation. Results revealed agricultural, ecologicaland cultural-spiritual practices that were synonymous to Satoyama and that of the Ainu. Research showedthat the development of Hokkaido resulted in a necessary increase in agriculture in the Ainu communitiessince it was no longer possible to live sustainably almost entirely from the gifts of nature; which holdstrue for indigenous peoples globally. We posit that these commonalities provide a viable entry point forthe promotion of Satoyama if it is to be used as a developmental model for promoting the introduction ofnew, effective and sustainable agricultural practices that are tailored to suit the local culture and existingtraditional knowledge, with a view of building sustainable indigenous communities globally, since it isinfrequent that modern systems practiced today mirror so closely traditional indigenous culture.